Analisis Harga Emas, Ukuran Perusahaan dan Profitabilitas Terhadap Pembiayaan Gadai Emas: Studi Empiris pada PT Bank Syariah Indonesia Tbk KCP Sukabumi Cicurug Setia Budi Periode 2021-2023 - Seli Lestari; Nor Norisanti; Resa Nurmala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine how much influence the Gold Price, Company Size, and Profitability have on Gold Pawn Financing at PT Bank Syariah Indonesia Tbk, KCP Sukabumi Cicurug Setia Budi for the period 2021-2023. The objects of research are Gold Price (X1), Company Size (X2) Profitability (X3) and Gold Pawn Financing (Y). The research uses descriptive and associative methods with a quantitative approach. The population in the study was the financial statements of PT Bank Syariah Indonesia Tbk, KCP Sukabumi Cicurug Setia Budi. Data analysis techniques used are classical assumption test, multiple linear regression analysis, multiple correlation coefficient, coefficient of determination, partial test (t test) and simultaneous test (f test). The results showed a relationship between Gold Price, Company Size, Profitability on Gold Pawn Financing of 0.766 the level of relationship including strong relationship criteria. Then the results of the partial test show that the price of gold has a positive and significant effect on gold pawn financing, company size has a negative and significant effect on gold pawn financing, profitability has a negative and significant effect on gold pawn financing.